DIGITALISASI REGISTRASI PENELITIAN KEMASYARAKATAN (LITMAS) KLIEN DEWASA DI BALAI PEMASYARAKATAN KELAS II LAHAT - fian angga (UNIVERSITAS STEKOM, 2022)
This research aims to solve the issues that occurred in Balai Pemasyarakatan Kelas II Lahat related to the not optimal registration of community research of adult clients in Balai Pemasyarakatan Kelas II Lahat. In this study the method used is with the APKL, USG and Fishbone Diagram methods in resolving the issues raised. The result of this research is the digitalization program of registration of community research adult clients provide convenience in registration services. The existence of this research, the issue of not optimal registration of community research adult clients in Balai Pemasyarakatan Kelas II Lahat can be resolved.